Bioavalaibilitas Nutrien pada Pakan Berserat dari Limbah Agroindustri dengan Teknologi Pengolahan yang Berbeda: Nutrient Bioavailability of Fibrous Agricultural Residues with Different Processing Technology - Setiadi, Deni; Titin Widiyastuti; Bambang Hartoyo; Tri Rachmanto Prihambodo (Jurnal Ilmu Nutrisi dan Teknologi Pakan, 2025)
The availability of forage in Indonesia is highly fluctuating, thereby hindering the sustainability of ruminant livestock farming. This study was conducted to optimize the potential of waste by improving the quality of nutrients contained therein through appropriate technology. An exploratory study was conducted by applying ammoniation technology using 3% urea and fermentation using 8% Trichoderma viride on several types of agro-industrial waste, including banana stems (ares), corn husks, peanut shells, durian skins, and pineapple skins. The parameters measured included dry matter digestibility, organic matter digestibility, volatile fatty acid concentration, and ammonia nitrogen (N-NH₃) production. The data were analyzed using descriptive methods. The results showed that ammoniation and fermentation treatments altered the nutrient characteristics of the feed materials and increased in vitro nutrient digestibility, particularly improving nutrient availability. Overall, these findings indicate that processing local feed sources through ammoniation and fermentation can improve nutrient availability and represent a promising strategy for developing efficient alternative feed sources for ruminants.